2015
DOI: 10.7860/jcdr/2015/12491.5966
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Commonly used Combination of Drugs in Primary Open Angle Glaucoma

Abstract: Background: Glaucoma is second cause of blindness in the world. The financial burden on the patient during long-term treatment is immense and affects the compliance to medications, thus visual morbidity. Objective:To analyse economic impact of three commonly used drug combinations (Dorzolamide + Timolol = DT; Brimonidine + Timolol = BT; Latanoprost+Timolol = LT) in primary open angle glaucoma. Materials and Methods:This observational, prospective study was undertaken at M & J Institute of Ophthalmology, Civil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Cost effectiveness was calculated by dividing the drug cost by the degree of the IOP reduction (mmHg), which is considered the efficacy of the drug, over the course of the study period [ 14 ]. The price per day of each drug multiplied by the number of days studied equals the drug cost during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Cost effectiveness was calculated by dividing the drug cost by the degree of the IOP reduction (mmHg), which is considered the efficacy of the drug, over the course of the study period [ 14 ]. The price per day of each drug multiplied by the number of days studied equals the drug cost during the study.…”
Section: Methodsmentioning
confidence: 99%
“…An Indian study compared three drug combinations, and found that the combination of Brimonidine/Timolol was most cost effective. They calculated cost-effectiveness by cost per mm IOP reduction [14].…”
Section: Resultsmentioning
confidence: 99%
“…Combinations of Dorzolamide plus Timolol, Brimonidine plus Timolol, and Latanoprost plus Timolol were compared. Brimonidine plus Timolol was found to be most cost effective among three groups [14].…”
Section: Fixed-combination Drugsmentioning
confidence: 94%
See 1 more Smart Citation
“…2 It has been shown that patients with glaucoma who do not receive adequate treatment have a chronic and progressive damage at the level of the optic nerve, which leads quickly and inexorably to blindness. 3 Glaucoma is the second cause of blindness in the world 4 and the first when it comes to irreversible blindness. 5…”
Section: Introductionmentioning
confidence: 99%